Sprain of the Subaxial Cervical Spine in Childhood - Rebecca F. Lyons; Kevin McSorely; Mutaz Jadaan; J. P. McCabe; Colin G. Murphy (Case Reports in Orthopedics)
Posterior atlantoaxial ligament disruption in children is a rare diagnosis. We present a case of a young girl with cervical spine posterior atlantoaxial ligament disruption post a fall from a climbing frame. Presenting with minimal symptoms other than neck pain, this case highlights the diagnostic difficulty and need for further radiological imaging in paediatric patients with neck pain post trauma.